Obstáculos para la entrada de solicitantes de asilo en Europa (el caso de Francia) - Julien-Laferrière, François (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2016)
To face the economic crisis, the European States since the 1970’s have been putting up barriers to the entrance of foreigners in their territories, considering each foreigner as a thief trying to pick the lock of the frontiers. This is translated into measures for restricting the entrance to the territory of the different States, the detention of those foreigners who do not fulfill the requirements for entry and their expulsion. Under these condictions, asylum petitioners find great difficulties for fleeing from their country of origin and finding refuge in a Europe which every day can, in lesser measure, pretend to be a land of asylum.